2010
DOI: 10.1016/j.jmaa.2009.10.014
|View full text |Cite
|
Sign up to set email alerts
|

C0-semigroups and mean ergodic operators in a class of Fréchet spaces

Abstract: It is shown that the generator of every exponentially equicontinuous, uniformly continuous C 0 -semigroup of operators in the class of quojection Fréchet spaces X (which includes properly all countable products of Banach spaces) is necessarily everywhere defined and continuous. If, in addition, X is a Grothendieck space with the Dunford-Pettis property, then uniform continuity can be relaxed to strong continuity. Two results, one of M. Lin and one of H.P. Lotz, both concerned with uniformly mean ergodic operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…In Section 4, using upper density and lower density, it is showed that the distributional chaoticity of µ p (T ) = {T t } t≥0 is equivalent to the distributional chaoticity of some T t 0 (t 0 > 0). This result is consistent with the similar conclusion in Banach space or other Frechet spaces (see References [17,27,29,31,33] and others). Then, some further results regarding C 0 -semigroups or Frechet spaces may be obtained in the future.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In Section 4, using upper density and lower density, it is showed that the distributional chaoticity of µ p (T ) = {T t } t≥0 is equivalent to the distributional chaoticity of some T t 0 (t 0 > 0). This result is consistent with the similar conclusion in Banach space or other Frechet spaces (see References [17,27,29,31,33] and others). Then, some further results regarding C 0 -semigroups or Frechet spaces may be obtained in the future.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, an extension of distributional chaos for a family of operators (including C 0 -semigroups) on Frechet spaces were proposed by Conejero [26]. For other studies of C 0 -semigroups or Frechet spaces see References [27][28][29][30][31][32][33][34] and others.…”
Section: Introductionmentioning
confidence: 99%